Compact Mesoscale Eddies in the South Brazil Bight - Cesar B. Rocha; Iury T. Simoes-Sousa (Remote Sensing, 2022)
Recent studies suggest that the South Brazil Bight (SBB) hosts strong westward propagating mesoscale eddies. We use 28 years of satellite altimetry data and a new Eddy Atlas to estimate how much of the eddy kinetic energy (EKE) observed in the SBB is accounted for by local eddies, generated in the Brazil Current (BC) region, versus remote eddies generated eastward of the BC region. First, we estimate a BC frontal density to obtain a robust definition of BC region. The BC front is well-defined throughout the SBB, occupying the region between the 200-m and 1000-m isobath, except in eddy hotspots downstream of sharp inflections of the continental slope, where the <semantics>EKE</semantics> far exceeds the mean kinetic energy (MKE). Compact, closed-contour mesoscale eddies account for 30–50% of the total <semantics>EKE</semantics> observed in the SBB, with local eddies accounting for most of the compact EKE in the BC region, defined as the area within 200 km of the 28-year mean BC front. Remote compact eddies account for less than 10% of the EKE observed in the BC region; compact eddies generated at long distances from the SBB, including eddies generated in the Southeastern Atlantic, contribute an insignificant fraction of <semantics>EKE</semantics> in the BC region.